Analisis Berita Acara Pemeriksaan (BAP) Kasus Perzinahan Kepolisian Negara Republik Indonesia Daerah Nusa Tenggara Timur Resor Lembata - Samara, Finsensius; Sina, Naurah Memeng; Reku, Albertino A. Noko; Thio, Imellany Anjelina; Langoday, Y. Antonio V; Doa, Familia S. (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the evidentiary strength of the witness’s examination report (BAP) in a case of alleged adultery as stipulated in Article 284 of the Criminal Code (KUHP). This study uses a normative juridical approach by analyzing the BAP of witness Mahmud Langoday, who was questioned by investigators from the Lembata Police. The study focuses on the elements of the crime of adultery, specifically the legal subject element, the element of sexual intercourse, the element of fault (mens rea), and the formal requirement of an absolute complaint offense. The analysis shows that although there is no direct evidence in the form of eyewitness testimony regarding the sexual intercourse, the series of interrelated indicative evidence meets the standard of sufficient preliminary proof to proceed to the investigation and summons stage.